Syndecan‐4 and stromal cell‐derived factor‐1 alpha functionalized endovascular scaffold facilitates adhesion, spreading and differentiation of endothelial colony forming cells and functions under flow and shear stress conditions. Issue 3 (8th October 2022) - Wu, Yidi; Yazdani, Saami K.; Bolander, Johanna Elin Marie; Wagner, William D.
Abstract: Acellular vascular scaffolds with capture molecules have shown great promise in recruiting circulating endothelial colony forming cells (ECFCs) to promote in vivo endothelialization. A microenvironment conducive to cell spreading and differentiation following initial cell capture are key to the eventual formation of a functional endothelium. In this study, syndecan‐4 and stromal cell‐derived factor‐1 alpha were used to functionalize an elastomeric biomaterial composed of poly(glycerol sebacate), Silk Fibroin and Type I Collagen, termed PFC, to enhance ECFC‐material interaction. Functionalized PFC (fPFC) showed significantly greater ECFCs capture capability under physiological flow. Individual cell spreading area on fPFC (1474 ± 63 μm 2 ) was significantly greater than on PFC (1187 ± 54 μm 2 ) as early as 2 h, indicating enhanced cell–material interaction. Moreover, fPFC significantly upregulated the expression of endothelial cell specific markers such as platelet endothelial cell adhesion molecule (24‐fold) and Von Willebrand Factor (11‐fold) compared with tissue culture plastic after 7 days, demonstrating differentiation of ECFCs into endothelial cells. fPFC fabricated as small diameter conduits and tested using a pulsatile blood flow bioreactor were stable and maintained function. The findings suggest that the new surface functionalization strategy proposed here results in an endovascular material with enhanced endothelialization.